A Study of the Materials Removal Mechanism of Grinding-Aided Electrochemical Discharge Machining of Metal Matrix Composites. Issue 5 (September 2018) - Liu, Jiangwen; Lin, Zhibiao; Guo, Zhongning; Jiang, Shuzhen; Yue, Taiman; Chen, Xiaolei
In order to research the workpiece materials removal mechanism of Grinding-assisted Electro-chemical Discharge Machining(G-ECDM) of Metal Matrix Composites (MMCs), a good deal of single pulse experiments has been performed in this paper. The crater volume, convex edge, debris, machined surface of G-ECDM have been taken into considerationand it turns out to be that the grinding effect removes the convex edge of the Electro-chemical Discharge Machining (ECDM) crater during the machining of MMCs, the result show that the material removal rate (MRR) of G-ECDM is much higher than that of ECDM and Electrical Discharge Machining (EDM). When compared to the normal ECDM process, it is found that though the Al4C3 phase can be detected in this ECDM condition, no Al4C3 are observed in the processed surface, which indicates a better surface quality. The reason of this phenomenonhas been analyzed theoretically and experimentally. Based on these results, mechanism of the G-ECDM of MMCs was disclosed in this study.